ANALYSIS OF TORQUE ROD BUSHING DAMAGE IN HINO 500 DUMP TRUCK UNITS AT PT XYZ - Arief Pambudi Ramadhan; Widia Setiawan; Radhian Krisnaputra; Ignatius Aris Hendaryanto; Bambang Hari Priyambodo (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
Bushing torque rod is a critical component of the suspension system in heavy-duty vehicles, functioning to absorb vibrations and maintain axle stability. In practice, repeated failures of this component have been observed in dump truck units operating with high hour meters, leading to reduced vehicle stability, driver discomfort, and increased downtime for maintenance. This study aims to analyze the relationship between operational hours and the severity of torque rod bushing damage, as well as to identify the most vulnerable positions in Hino 500 dump trucks at PT XYZ. The research applied a quantitative approach using descriptive statistics, Pearson correlation, and simple linear regression. Data were collected from 50 dump truck units, covering six bushing positions: Front Upper, Rear Upper, Front Left, Front Right, Rear Left, and Rear Right. The results showed that Rear Left and Rear Right bushings had the highest frequency of severe damage, each at 70%, followed by Front Left (50%) and Front Right (44%), while Front Upper and Rear Upper recorded the lowest rates. Regression analysis revealed a strong positive correlation between operational hours and damage severity. The developed model predicts that for every 1,000 additional hours of operation, the potential for bushing failure increases by a quantifiable measure. Consequently, a preventive replacement strategy is recommended at 6,000–7,000 operational hours, particularly for the rear axle positions, to mitigate downtime